Influence of shopping orientation and store image on patronage of furniture store / Yasmin Hassan, Nik Maheran Nik Muhammad and Hatinah Abu Bakar - Hassan, Yasmin; Nik Muhammad, Nik Maheran; Abu Bakar, Hatinah (2010)
Knowledge on furniture consumers' retail patronage will promote and enhance efforts to increase sales at furniture stores and could guide future research. This research therefore was proposed to develop a general model of retail patronage and to empirically test the relationships proposed in the model in the context of furniture market. The objectives of the study include I) to review existing retail patronage models and related literature 2) to develop a gtmeral framework ofretail patronage behavior and 3) to test the model in the furniture store shopping patterns. Based on a review of the literature the study proposed to adapt Darden's patronage model of consumer behavior. 115 data were collected through survey questionnaires and the underlying relationship among the variables that characterize consumers' patronage behavior towards furniture was studied. Dimensions for shopping orientation was found consistent with the previous literature where four dimensions of personal, economic, ethical and apathetic shoppers were identified. The result shows that personal shoppers were found to have ethnocentric life style, ethical shoppers were associated to geocentric and apathetic shoppers were polycentric. Consumers also was found to prefer a store with the image of having quality product followed with price and services. The results also showed that patronage behavior has positive relationship to personal and ethical shoppers while economic and apathetic shoppers show no significant relatioriship with patronage. The findings definitely will provide the practitioners to strategize their marketing by ensuring that they focus more on relationship marketing by having that personal touch with their consumers as the most loyal furniture customers are personalize and ethical consumers ..